The impact of international trade, foreign direct investment, and demographic structure on the environmental quality of human well-being: evidence from Bhutan - Ye, Zhu; Wang, Han; Chen, Hongjin; Yu, Yong (Frontiers in Human Dynamics, 2025)
Based on the environmental quality data pertaining to human well-being in Bhutan from 2002 to 2022, the ARDL-ECM model was employed to examine the long-term equilibrium and short-term dynamic relationships between international trade, foreign direct investment, and demographic structure with Bhutan’s per capita ecological footprint. Additionally, the Granger causality test was utilized to further investigate these relationships. The results showed that: During the study period, the environmental quality of human well-being in Bhutan was deteriorating continuously; The increase of international trade can increase the per capita ecological footprint of Bhutan, which leads to the decline of Bhutan’s environmental quality, and it is also the Granger cause of the change in Bhutan’s per capita ecological footprint. Foreign direct investment and demographic structure move in the opposite direction of Bhutan’s per capita ecological footprint. This serves as a point of reference for policymakers when formulating pertinent strategies, and offers a theoretical foundation and practical guidance for other nations in their pursuit of sustainable development pathways.